Point-of-care application of diaphragmatic ultrasonography in the emergency department for the prediction of development of respiratory failure in community-acquired pneumonia: A pilot study - Chu, Sheng-En; Lu, Jian-Xun; Chang, Shi-Chuan; Hsu, Kuang-Hung; Goh, Zhong Ning Leonard; Seak, Chen-Ken; Seak, Joanna Chen-Yeen; Ng, Chip-Jin; Seak, Chen-June (Frontiers in Medicine, 2022)
Background Early recognition of patients with community-acquired pneumonia (CAP) at risk of poor outcomes is crucial. However, there is no effective assessment tool for predicting the development of respiratory failure in patients with CAP. Diaphragmatic ultrasonography (DUS) is a novel technique developed for evaluating diaphragmatic function via measurements of the diaphragm thickening fraction (DTF) and diaphragm excursion (DE). This study evaluated the accuracy of DUS in predicting the development of respiratory failure in patients with CAP, as well as the feasibility of its use in the emergency department (ED) setting. Materials and methods This was a single-center prospective cohort study. We invited all patients with ED aged ≥ 20 years who were diagnosed with CAP of pneumonia severity index (PSI) SIe diagnosed with CAP of pneumonia severe with respiratory failure or septic shock were excluded. Two emergency physicians performed DUS to obtain DTF and DE measurements. Data were collected to calculate PSI, CURB-65 score, and Infectious Diseases Society of America/American Thoracic Society severity criteria. Study endpoints were taken at the development of respiratory failure or 30 days post-ED presentation. Continuous variables were analyzed using T-tests, while categorical variables were analyzed using chi-square tests. Further logistic regression and receiver operating characteristic curve analyses were performed to examine the ability to predict the development of respiratory failure. Intra- and inter-rater reliability was examined with intraclass correlation coefficients (ICCs). Results In this study, 13 of 50 patients with CAP enrolled developed respiratory failure. DTF was found to be an independent predictor (OR: 0.939, p = 0.0416). At the optimal cut-off point of 23.95%, DTF had 69.23% of sensitivity, 83.78% of specificity, 88.57% of negative predictive value, and 80% of accuracy. Intra- and inter-rater analysis demonstrated good consistency (intra-rater ICC 0.817, 0.789; inter-rater ICC 0.774, 0.781). Conclusion DUS assessment of DTF may reliably predict the development of respiratory failure in patients with CAP presenting to the ED. Patients with DTF > 23.95% may be considered for outpatient management.